Improving Reading Comprehension Skills in English through Interactive Animation Video Based on Project Based Learning for Slow Learner Students in Grade VII of SMP Negeri 2 Karangan - Putri Ayu Kusuma Dewi; Ishartiwi Ishartiwi (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This study aims to examine the process and improvement of reading comprehension skills among slow learner students in Grade VII at SMP Negeri 2 Karangan through the use of interactive animation video media based on the Project Based Learning (PjBL) model. Employing the Classroom Action Research (CAR) method following the Kemmis and McTaggart model, the study was conducted in two cycles with six slow learner students as research subjects. The observation results indicated an improvement from 89.58% in Cycle I to 100% in Cycle II. The average reading comprehension score increased from 65 to 83, with the percentage of students achieving the minimum mastery criteria rising from 67.85% to 89.28% with a difference of 18 points increase. These findings demonstrate that interactive animation video media based on PjBL effectively enhances both student engagement and learning outcomes, particularly in understanding English texts. This success was supported by the active role of the teacher in adapting the PjBL syntax to meet the specific needs of the slow learner students.